Vectorized Enterprise Knowledge Systems: Transforming Organizational Intelligence Using Retrieval-Augmented AI - Ananda Kumar Dey (Malikussaleh University, Aceh, Indonesia, 2026)
Large-scale liquefied natural gas (LNG) projects represent some of the most logistically complex undertakings in industrial engineering, requiring the coordinated fabrication of tens of thousands of pipe spools across geographically distributed facilities while maintaining strict cost, schedule, quality, and regulatory requirements. Despite advances in digital manufacturing, limited research has examined how integrated material requirements planning (MRP) systems support synchronized fabrication at mega-project scale. This paper investigates the implementation of an integrated MRP framework at Fabrication Manufacturing facilities supporting LNG projects, where approximately 100,000 pipe spools were fabricated across six production facilities using a centralized planning and distributed execution architecture. The proposed framework aligns with Advanced Work Packaging (AWP) principles recommended by the Construction Industry Institute (CII), ISA-95 enterprise-control integration standards, and ASME/API engineering compliance requirements to enhance coordination between planning, procurement, inventory management, and shop-floor execution. The implementation introduces a bidirectional integration model between the MRP system and the Manufacturing Execution System (MES), enabling real-time synchronization of production schedules, material availability, fabrication status, and inventory data across all participating facilities. Furthermore, a centralized pre-buy material distribution strategy minimizes procurement uncertainty and improves supply chain responsiveness. Empirical results demonstrate an 18–25% reduction in procurement lead time, a 20–30% increase in fabrication productivity through AWP-aligned sequencing, and improved schedule reliability across multi-site operations. The integrated digital planning architecture also enhanced resource utilization, reduced production bottlenecks, and strengthened cross-facility coordination. These findings establish integrated MRP implementation as a critical enabler of efficient mega-scale LNG fabrication delivery and provide a practical, scalable, and replicable framework for engineering, procurement, and construction (EPC) contractors managing highly complex industrial projects